2022
DOI: 10.3899/jrheum.211246
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy Computed Tomography Has Additional Prognostic Value Over Clinical Measures in Gout Including Tophi: A Systematic Literature Review

Abstract: Objective This Systematic Literature Review determined whether there is clinical utility for Dual Energy CT (DECT) to inform on prognosis for gout patients. With DECT, individualized treatment plans could be developed based on the patient's unique urate burden, with DECT used as a clinical outcome measure in gout management. Methods To evaluate DECT as a reliable, valid, and sensitive prognostic instrument, a librarian-assisted search was undertaken in PubMed and EMBASE for articles on gout and DECT informing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…13 A systematic review in 2022 showed that DECT images are reliably interpreted with intra-rater intraclass correlation coefficients ranging from 0.86 to 1.00. 30 DECT overall had very good sensitivity and specificity in established gout when compared with joint aspiration, with ranges from 0.78 to 0.89 and 0.84 to 1.00, respectively. DECT also performed very well against clinical criteria, with a pooled sensitivity and specificity of 0.81 (95% confidence interval [CI], 0.77–0.86) and 0.91 (95% CI, 0.85–0.95).…”
Section: Specific Forms Of Arthropathiesmentioning
confidence: 96%
See 4 more Smart Citations
“…13 A systematic review in 2022 showed that DECT images are reliably interpreted with intra-rater intraclass correlation coefficients ranging from 0.86 to 1.00. 30 DECT overall had very good sensitivity and specificity in established gout when compared with joint aspiration, with ranges from 0.78 to 0.89 and 0.84 to 1.00, respectively. DECT also performed very well against clinical criteria, with a pooled sensitivity and specificity of 0.81 (95% confidence interval [CI], 0.77–0.86) and 0.91 (95% CI, 0.85–0.95).…”
Section: Specific Forms Of Arthropathiesmentioning
confidence: 96%
“…DECT also performed very well against clinical criteria, with a pooled sensitivity and specificity of 0.81 (95% confidence interval [CI], 0.77-0.86) and 0.91 (95% CI, 0.85-0.95). 30 A study comparing the diagnostic accuracies of dualsource DECT and US in patients with different gouty disease durations reported that the sensitivities of DECT for gout within 1 year, 1 to 3 years, and > 3 years are 26.6%, 66.6%, and 90%, respectively. 31 They also revealed that the sensitivity of US is remarkably higher than that of dual-source DECT in early gout and suggested US as the first choice to diagnose early-stage gout.…”
Section: Goutmentioning
confidence: 99%
See 3 more Smart Citations